Role of addiction and stress neurobiology on food intake and obesity - Sinha, Rajita (Biol Psychol, 2017)
The US remains at the forefront of a global obesity epidemic with a significant negative impact on public health. While it is well known that a balance between energy intake and expenditure is homeostatically regulated to control weight, growing evidence points to multifactorial social, neurobehavioral and metabolic determinants of food intake that influence obesity risk. This review presents factors such as the ubiquitous presence of rewarding foods in the environment and increased salience of such foods that stimulate brain reward motivation and stress circuits to influence eating behaviors. These rewarding foods via conditioned and reinforcing effects stimulate not only metabolic, but also stress hormones, that, in turn, hijack the brain emotional (limbic) and motivational (striatal) pathways, to promote food craving and excessive food intake. Furthermore, the impact of high levels of stress and trauma and altered metabolic environment (e.g. higher weight, altered insulin sensitivity) on prefrontal cortical self-control processes that regulate emotional, motivational and visceral homeostatic mechanisms of food intake and obesity risk are also discussed. A heuristic framework is presented in which the interactive dynamic effects of neurobehavioral adaptations in metabolic, motivation and stress neurobiology may further support food craving, excessive food intake and weight gain in a complex feed-forward manner. Implications of such adaptations in brain addictive-motivational and stress pathways and their effects on excessive food intake and weight gain are discussed to highlight key questions that requires future research attention in order to better understand and address the growing obesity epidemic.